2005
DOI: 10.1111/j.1600-6143.2005.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Procurement of Kidneys with Multiple Renal Arteries is Associated with Increased Ureteral Complications in the Recipient

Abstract: This study investigates the effect of renal artery multiplicity on donor and recipient outcomes after laparoscopic donor nephrectomy. Three-hundred and sixty-one sequential procedures were performed over a 4-year period. Forty-nine involved accessory renal arteries; of these, 36 required revascularization and 13 were small polar vessels and ligated. The 312 remaining kidneys with single arteries served as controls. Study variables included operative times, blood loss, hospital stay, graft function and donor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
90
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 31 publications
10
90
3
Order By: Relevance
“…When proteinuria and albuminuria were evaluated, there was a trend toward higher levels of total urine protein and albumin in donors who were obese at donation, and the incidence of abnormal proteinuria was significantly increased in the obese; however, the incidence of abnormal albuminuria was not significantly different between the two groups. These findings corroborate other reports demonstrating relative preservation of renal function in obese donors on short-term follow-up (19,20,22) but differ from several large-scale population studies that examined the impact of obesity on renal function. For example, a recent study which examined Ͼ350,000 adult patients in the Kaiser-Permanente system in California found that obese patients had a significantly increased incidence of ESRD compared with normalweight control subjects.…”
Section: Discussionsupporting
confidence: 79%
“…When proteinuria and albuminuria were evaluated, there was a trend toward higher levels of total urine protein and albumin in donors who were obese at donation, and the incidence of abnormal proteinuria was significantly increased in the obese; however, the incidence of abnormal albuminuria was not significantly different between the two groups. These findings corroborate other reports demonstrating relative preservation of renal function in obese donors on short-term follow-up (19,20,22) but differ from several large-scale population studies that examined the impact of obesity on renal function. For example, a recent study which examined Ͼ350,000 adult patients in the Kaiser-Permanente system in California found that obese patients had a significantly increased incidence of ESRD compared with normalweight control subjects.…”
Section: Discussionsupporting
confidence: 79%
“…Carter et al also showed a higher rate of ureteral complications in patients with multiple arteries (17% vs 3%) when analyzing 361 LDN. The authors concluded that this higher rate could be a result of insufficient perfusion in the kidney's lower pole, probably related to excessive traction or cautery lesion during dissection (14). However, other papers analyzing LDN did not show a higher incidence of vascular and ureteral complications when harvesting kidneys with multiple arteries (16)(17)(18).…”
Section: Discussionmentioning
confidence: 76%
“…The requirement for complicated vascular reconstruction and more difficult anastomosis at the time of implantation impose additional ischemic injury and subsequent reperfusion injury (13). This extended dissection and the need for back-table reconstruction have been shown, by some authors, to be associated with an increased risk for urological and vascular complications (9,14,15). Roza et al analyzed 42 living donor open nephrectomies with multiple arteries and observed 8 patients (19%) with urological complications and 3 (7%) with vascular complications (9).…”
Section: Discussionmentioning
confidence: 99%
“…(18) In addition, it could also reduce the increased warm ischemia times and the consequent ureteral complications associated with multiple artery LDNs. (19) Current methods of vessel identification and differentiation in laparoscopy are limited to visual cues (color, pulsations, etc.). This, however, is highly subjective and dependent on surgeon experience.…”
Section: Discussionmentioning
confidence: 99%